Future direction of wound dressing research: Evidence From the bibliometric analysis. (23rd September 2022) - Ho, Yuh-Shan; Sharmin, Afsana Al; Islam, Mohammad Tajul; Halim, AFM Fahad
A bibliometric analysis based on the Science Citation Index Expanded database from 1991 to 2020 was performed to obtain insight into the future direction of wound dressing research. The study focused on the publication's performance in terms of yearly outputs and citations, mainstream journals, categories of the Web of Sciences, top countries, leading institutions, trends in research, and hotspots. A summary of the most commonly used keywords extracted from words in the paper title analysis, authors' keyword analysis, and KeyWords Plus analysis served as the foundation for determining current research priorities and future trends. The findings revealed that the annual output of the corresponding scholarly articles remained more or less the same during the first decade, followed by a rapid increase in the remaining period of the study. Tissue engineering would be the future of the existing wound dressing research. Biomaterials and electrospinning are gaining importance as raw materials and fabrication techniques for wound dressing. Advanced wound dressings with antimicrobial functionality and sustained drug release properties are becoming a popular research avenue in the wound dressing research field.